Sodium sulfite and extrusion affect the nutritional value of soybean products for nursery pigs - L L Burnham; I H Kim; Robert H Hines; Terry L Gugle; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1995)
Extruded soybeans improved rates and efficiencies of gain when fed to nursery pigs in place of soybean meal (SBM). Sodium sulfite (an extrusion aid) increased extruder throughput and improved d 13 to 35 and overall efficiency of growth in pigs fed extruded soybeans and unextruded SBM. Further research is needed to determine if greater sodium sulfite concentrations will continue to increase extruder throughput and to elucidate the mechanism for improved growth performance of pigs fed sodium sulfite with unextruded SBM.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Nursery; Soybeans; Processing